Contribution of the Role of Health Cadres in the Prevention of Stunting in Toddlers - Ahmad, Haslinah; Alwi, Fahrizal; Hadi, Anto J (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Stunting in toddlers is still a serious public health problem in Indonesia. Stunting can cause various adverse effects on children's health, such as growth and development problems, impaired cognitive function, and increases risk of disease in adulthood. This study was to analyze the role of health cadres in preventing stunting in toddlers. The study was cross-sectional with a sample of 200 cadres selected by exhaustive sampling. Data were collected by questionnaire and analyzed using the Chi-square test and logistic regression. The results showed that there was a significant relationship between employment status (p=0.001), attitude (p=0.001), perception (p=0.001), marital status (p=0.047), the competence of health cadres and the role of cadres in stunting prevention (p=0.001). The variable that contributes the most to the role of cadres in stunting prevention is the competence of cadres with Exp. (B)=4.914. The study shows that the role of health cadres in preventing stunting is important for improving the nutritional status of toddlers. Therefore, it is necessary to make efforts to improve the competence of health cadres, provide a positive perception of work, and improve the attitude of health cadres towards stunting prevention through training and skills provision for health cadres.